Firm-level Perspectives on State–Business Relations in Africa: The Food-processing Sector in Kenya, Tanzania and Zambia. Issue 1 (2nd January 2017) - Charles, Goodluck; Jeppesen, Søren; Kamau, Paul; Kragelund, Peter
Abstract : Experiences from developed and emerging economies inform us that close state–business relations (SBRs) are crucial for economic development and structural transformation. Based on the positive experiences from other parts of the world, most African governments have begun processes to establish collaborative SBRs. Amongst other initiatives, these processes include amendments to existing laws to facilitate public–private interaction, direct support to existing business associations (BAs). This article draws on an analysis of survey data from 210 local firms, complemented with qualitative data from interviews with 41 firms, 20 key informants and a range of secondary sources on the food-processing sectors of Kenya, Tanzania and Zambia. The article shows that businesses in these countries have limited policy influence, find policies and programmes to be inadequate when targeting the needs and requirements of local businesses and that BAs in these countries are poorly organised. In spite of initiatives taken by the states and other actors, including an increase in the number of formal relations between state and businesses, it is difficult to conclude whether SBRs are collaborative or collusive. The article contributes to the existing SBR literature by adding a firm-level perspective and by enhancing our knowledge on the usefulness of key theoretical approaches to these issues in an African context.